1991
DOI: 10.1021/bi00244a031
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic state of the a3 center of cytochrome c oxidase and some of its derivatives

Abstract: The temperature dependence of the magnetic susceptibility was used to investigate the nature of the coupling between cytochrome alpha 3 and CuB in resting and oxidized cyanide- and formate-bound cytochrome oxidase. Resting and formate-bound enzymes were found to have strong antiferromagnetic coupling with an S = 5/2 cytochrome alpha 3, results that were independent of the dispersing detergent and the enzyme isolation method. The cyanide-bound enzyme was heterogeneous, with a minor fraction showing intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…In the current study, the increased information of the multifield saturation magnetization method results in a clear distinction between the fast and slow forms of oxidized cytochrome c oxidase. A previous susceptibility study was unable to distinguish these forms of the enzyme (Barnes et al, 1991).…”
mentioning
confidence: 77%
“…In the current study, the increased information of the multifield saturation magnetization method results in a clear distinction between the fast and slow forms of oxidized cytochrome c oxidase. A previous susceptibility study was unable to distinguish these forms of the enzyme (Barnes et al, 1991).…”
mentioning
confidence: 77%
“…Theoretical models based on both the strong and weak coupling limits have also been used to interpret Mössbauer and magnetic susceptibility data on cytochrome c oxidase (Moss et al, 1978;Dunham et al, 1983;Kent et al, 1983;Tweedle et al, 1978;Day et al, 1993;Barnes et al, 1991;Rusnak et al, 1987) as well as on heme-copper-bridged assemblies pertinent to cytochrome c oxidase (Kauffmann et al, 1997). Mössbauer spectra of the a 3 -Cu B site of oxidized Thermus thermophilus c 1 aa 3 could be simulated equally well in terms of a weak (J Ϸ 1 cm Ϫ1 ) or a strong (J Ͼ 7 cm Ϫ1 ) coupling (Rusnak et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, in the slow form, the magnetic coupling and zero-field-splitting parameters are quantitatively different from those of the fast enzyme and result in the observation of an active EPR spectrum. 7,14,15 Dual-mode X-band EPR spectra of fluoride cytochrome bo 3 show broad, fast relaxing features with a similar pattern of bands: a weak derivative signal below 100 mT (g ≈ 12) accompanied by a broad band in the 200−250 mT region (g ≈ 3.2). 10,16−18 Simulations of dual-mode spectra indicated that the metal ions were weakly coupled by an anisotropic exchange interaction of |J| ≈ 1 cm −1 .…”
Section: ■ Introductionmentioning
confidence: 91%
“…In the oxidized C c O, fast and slow forms are defined according to the rate of reaction of the enzyme with exogenous anionic ligands such as fluoride (F – ), cyanide (CN – ), and formate (HCOO – ). , Both forms of the enzyme have been proposed to consist of the Fe III –X–Cu II moiety, in which X represents a bridging ligand that modulates the coupling between two metal ions. , Naturally occurring X groups, which have been proposed, include oxide (O 2– ), hydroxide (OH – ), cyanide (CN – ), formate (HCOO – ), chloride (Cl – ), fluoride (F – ), and an imidazolate group . Mössbauer spectroscopic measurements of Paracoccus denitrificans and bovine heart C c O revealed that high-spin Fe 3+ ( S = 5/2) was strongly coupled with Cu 2+ ( S = 1/2), resulting in no EPR signal in the fast form of the enzyme. , However, in the slow form, the magnetic coupling and zero-field-splitting parameters are quantitatively different from those of the fast enzyme and result in the observation of an active EPR spectrum. ,, Dual-mode X-band EPR spectra of fluoride cytochrome bo 3 show broad, fast relaxing features with a similar pattern of bands: a weak derivative signal below 100 mT ( g ≈ 12) accompanied by a broad band in the 200–250 mT region ( g ≈ 3.2). , Simulations of dual-mode spectra indicated that the metal ions were weakly coupled by an anisotropic exchange interaction of | J | ≈ 1 cm –1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation